MODERN HISTORIOGRAPHY OF THE «PROTEST SENTIMENTS» OF THE RUSSIAN PEASANTRY 1902–1922. - Frolov V.N. (Вестник Брянского государственного университета)
«Protest sentiments» are a complex phenomenon. «Protest sentiments» has not been an object of study by historians in the sense of a psychological, socio-historical phenomenon for a long time. Special attention was paid to the peasant economy and the peasant movement of 1905–1907 and 1917–1922 or 1902–1922 (the years of the Russian peasant revolution) in Russia. The problems of psychological and social history and mental aspects were touched upon, as a rule, partially and episodically within the framework of determining the interests of peasants. A separate study of peasant consciousness and peasant worldview begins in the 70s–80s of the twentieth century. These works did not aim to study specifically the «protest sentiments» at that time. The aim of the article is to analyze and summarize the modern historiography of peasant protest in the context of studying "protest sentiments". Historical-comparative and historical-systemic methods are used. Most researchers agree on the objectivity of the factors of peasant protest and designating a generally consonant set of subjective factors. The «protest sentiments» of peasants are interpreted as a special phenomenon in studies on peasant consciousness and mentality. Moreover, «protest» is seen as a reaction of the peasantry to an attempt by the state or modernization processes to interfere in their world, and as an integral part of the peasant mentality. Most authors conclude that the peasantry advocated improving their socio-economic situation and preserving themselves as a social stratum.